PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA - Rahmadan Arjunaldi; Meiffa Herfianti (Yayasan Insani Mandiri Santani, 2026)
This research is based on the need to further explore how the leadership style of superiors and the characteristics of the organizational culture in this environment influence employee job satisfaction levels. This initial field data strengthens the need for systematic research to produce appropriate recommendations in developing human resource management policies at PT PLN Icon Plus Kota Bengkulu. The research method used is a quantitative method with a survey approach. Data were collected through questionnaires and analyzed using multiple linear regression analysis, validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results of the study show that From the results of the t test, the regression coefficient value of the Leadership Style variable (X1) (t count) is 2.135 with a t table of 1.669, the t count value ˃ t table and significance of 0.04 ˂ 0.05 means that the Leadership Style variable (X1) has a significant effect on the Job Satisfaction of employees of PT. PLN Icon Plus Bengkulu City (Y). For the t test value, the regression coefficient value of the Organizational Culture variable (X2) (t count) is 2.303 with a t table of 1.669, the t count value ˃ t table and significance of 0.02 ˂ 0.05 means that the Organizational Culture variable (X2) has a significant effect on the Job Satisfaction of employees of PT. PLN Icon Plus Bengkulu City (Y). The calculated F value is 13.950˃, the F table value is 3.993 and the significance is 0.000˂ 0.05. H3 is accepted and H0 is rejected. It can be concluded that the variables of Leadership Style (X1) and Organizational Culture (X2) have a significant effect on the Job Satisfaction of PT. PLN Icon Plus Kota Bengkulu employees (Y). With an Adjusted R Square value of 0.482, it shows that 48.2% of job satisfaction can be explained by the variables of leadership style and organizational culture. Keywords: Leadership Style, Organizational Culture and Employee Job Satisfaction